Synaptic interactions between perifornical lateral hypothalamic area, locus coeruleus nucleus and the oral pontine reticular nucleus are implicated in the stage succession during sleep-wakefulness cycle - Nunez, Angel; Tortorella, Silvia; Rodrigo-Angulo, Margarita L.; Garzón, Miguel (Frontiers in Neuroscience, 2013)
The perifornical area in the posterior lateral hypothalamus (PeFLH) has been implicated in several physiological functions including the sleep-wakefulness regulation. The PeFLH area contains several cell types including those expressing orexins (Orx; also known as hypocretins), mainly located in the PeF nucleus. The aim of the present study was to elucidate the synaptic interactions between Orx neurons located in the PeFLH area and different brainstem neurons involved in the generation of wakefulness and sleep stages such as the locus coeruleus (LC) nucleus (contributing to wakefulness) and the oral pontine reticular nucleus (PnO) nucleus (contributing to REM sleep) Anatomical data demonstrated the existence of a neuronal network involving the PeFLH area, LC and the PnO nuclei that would control the sleep-wake cycle. Electrophysiological experiments indicated that PeFLH area had an excitatory effect on LC neurons. PeFLH stimulation increased the firing rate of LC neurons and induced an activation of the EEG. The excitatory effect evoked by PeFLH stimulation in LC neurons was blocked by the injection of the Orx-1 receptor antagonist SB-334867 into the LC. Similar electrical stimulation of the PeFLH area evoked an inhibition of PnO neurons by activation of GABAergic receptors because the effect was blocked by bicuculline application into the PnO. Our data also revealed that the LC and PnO nuclei exerted a feedback control on neuronal activity of PeFLH area. Electrical stimulation of LC facilitated firing activity of PeFLH neurons by activation of catecholaminergic receptors whereas PnO stimulation inhibited PeFLH neurons by activation of GABAergic receptors. In conclusion, Orx neurons of the PeFLH area seem to be an important organizer of the wakefulness and sleep stages in order to maintain a normal succession of stages during the sleep-wakefulness cycle.